Surfen is a broad-spectrum calcium channel inhibitor with analgesic properties in mouse models of acute and chronic inflammatory pain - Rivas-Ramirez, Paula; Gadotti, Vinicius M; Zamponi, Gerald W; Weiss, Norbert (Pflugers Archiv, 2017)
Multiple voltage-gated calcium channels (VGCCs) contribute to the processing of nociceptive signals in primary afferent fibers. In addition, alteration of calcium channel activity is associated with a number of chronic pain conditions. Therefore, VGCCs have emerged as prime target for the management of either neuropathic or inflammatory pain, and selective calcium channel blockers have been shown to have efficacy in animal models and in the clinic. However, considering that multiple calcium channels contribute pain afferent signaling, broad-spectrum inhibitors of several channel isoforms may offer a net advantage in modulating pain. Here, we have analyzed the ability of the compound surfen to modulate calcium channels, and assessed its analgesic potential. We show that surfen is an equipotent blocker of both low- and high-voltage-activated calcium channels. Furthermore, spinal (intrathecal) delivery of surfen to mice produces sustained analgesia against both acute and chronic pain. Collectively, our data establish surfen as a broad-spectrum calcium channel inhibitor with analgesic potential, and raise the possibility of using surfen-derived compounds for the development of new pain-relieving drugs.
Keywords: Calcium channel blocker; Inflammation; Calcium Channel Blockers; Analgesics; Chronic Disease; chronická nemoc; zánět; vápník; neuralgie; myši inbrední C57BL; Calcium Signaling; mužské pohlaví; Disease Models, Animal; Pain; DRG neuron; blokátory kalciových kanálů; Calcium; modely nemocí na zvířatech; vápníková signalizace; zvířata; Humans; Neuralgia; Surfen; Calcium channel; Chronic Pain; Inflammatory pain; analgetika; Mice, Inbred C57BL; lidé; Male; chronická bolest; Animals